Shear Modulus Dispersion in Cracked and Fluid‐Saturated Quartzites: Experimental Observations and Modeling. Issue 4 (13th April 2018) - Schijns, Heather; Jackson, Ian; Schmitt, Douglas R.
Abstract: The effect of pore fluids on acoustic wave dispersion in rocks with low aspect ratio crack porosity is important for the interpretation of laboratory and field observations in hard rock mineral exploration environments. Here we make laboratory measurements of shear modulus dispersion at frequencies 0.01–1 Hz and at 1 MHz with different saturating fluids (dry, argon, and water saturated) in two thermally cracked quartzite samples with ~2% total porosity. Measurements are made across a range of effective pressures (10–150 MPa), with the resulting very low permeabilities of the samples varying from 1–300 × 10 −21  m 2 . Moduli across the 0.01–1 Hz band were typically independent of frequency. The shear moduli measured at sub‐Hz frequencies are unaffected by fluid saturation, as expected for the saturated isobaric (Gassmann) regime. In marked contrast, water saturation of the cracked rocks results in very large increases in the shear moduli measured at 1 MHz and low effective pressures, indicative of saturated isolated conditions. Thus, at an effective pressure of 20 MPa, the shear moduli for the two water‐saturated quartzites increase by 74% and 98% from 1 Hz to 1 MHz. The contrast in elastic moduli between dry and water‐saturated conditions is well represented by the theoretical model developed by Walsh and others. The observed dispersion highlights the need for care in seismological application of results obtained at MHz frequencies from laboratory ultrasonic measurements. Key Points: Water saturation of the thermally cracked quartzites is experimentally observed to cause strong shear modulus dispersion between seismic and ultrasonic frequencies A mean crack aspect ratio of ~0.001 is inferred from the magnitude of the shear modulus deficit and the pressure dependence of the shear moduli Thermal cracking of essentially monominerallic quartzites induces substantial crack densities approaching 0.5 at low differential pressures